A randomised controlled trial of spinal manipulative therapy in acute low back pain. Issue 9 (5th September 2008) - Jüni, P; Battaglia, M; Nüesch, E; Hämmerle, G; Eser, P; van Beers, R; Vils, D; Bernhard, J; Ziswiler, H-R; Dähler, M; Reichenbach, S; Villiger, P M
Abstract : Objective: To determine whether treatment with spinal manipulative therapy (SMT) administered in addition to standard care is associated with clinically relevant early reductions in pain and analgesic consumption. Methods: 104 patients with acute low back pain were randomly assigned to SMT in addition to standard care (n = 52) or standard care alone (n = 52). Standard care consisted of general advice and paracetamol, diclofenac or dihydrocodeine as required. Other analgesic drugs or non-pharmacological treatments were not allowed. Primary outcomes were pain intensity assessed on the 11-point box scale (BS-11) and analgesic use based on diclofenac equivalence doses during days 1–14. An extended follow-up was performed at 6 months. Results: Pain reductions were similar in experimental and control groups, with the lower limit of the 95% CI excluding a relevant benefit of SMT (difference 0.5 on the BS-11, 95% CI −0.2 to 1.2, p = 0.13). Analgesic consumptions were also similar (difference −18 mg diclofenac equivalents, 95% CI −43 mg to 7 mg, p = 0.17), with small initial differences diminishing over time. There were no differences between groups in any of the secondary outcomes and stratified analyses provided no evidence for potential benefits of SMT in specific patient groups. The extended follow-up showed similar patterns. Conclusions: SMT is unlikely to result in relevant early pain reduction in patients with acute low back pain.